Relevansi Konstruktivisme Sosial Lev Vygotsky terhadap Kurangnya Peran Orang Tua dalam Pendidikan Moral Anak di Indonesia - Retnaningsih, Aritiyas Panca (Program Studi Filsafat Agama Hindu IAHN Gde Pudja Mataram, 2024)
This article is based on a qualitative research in the field of philosophy of education, using social constructivism theory as the formal object and the phenomenon of the lack of parental role in children's moral education in Indonesia as the material object. Data were obtained through a literature review of works related to the objects. The author of this article aims to understand the relevance of social constructivism theory in the thinking of Lev Vygotsky regarding the lack of parental role in children's moral education in Indonesia. The results of the analysis lead to the following conclusions: 1) Social constructivism theory emphasizes the importance of social interaction in the formation of children's or individuals' knowledge structures. This theory originated from a Russian philosopher and psychologist named Lev Vygotsky. Vygotsky introduced the concept of the zone of proximal development to indicate the actual development level of a child compared to their potential development level under adult guidance. 2) The lack of parental role in children's moral education has implications for the hindered social and moral development of children. Based on Lev Vygotsky's zone of proximal development, there is a need for active parental guidance in providing moral guidance to children, not only by teaching moral concepts but also by being living examples of those values.